Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Sure! To solve the expression [tex]\(\frac{1 + \tan^2 A}{1 + \cot^2 A}\)[/tex], let's break it down step-by-step using trigonometric identities.
### Step 1: Understand the trigonometric identities involved
1. Tangent and Cotangent:
- [tex]\(\tan A = \frac{\sin A}{\cos A}\)[/tex]
- [tex]\(\cot A = \frac{\cos A}{\sin A}\)[/tex]
2. Pythagorean Identity for Tangent:
- [tex]\(1 + \tan^2 A = \sec^2 A\)[/tex]
3. Pythagorean Identity for Cotangent:
- [tex]\(1 + \cot^2 A = \csc^2 A\)[/tex]
### Step 2: Substitute the identities
Replace [tex]\(1 + \tan^2 A\)[/tex] and [tex]\(1 + \cot^2 A\)[/tex] with their equivalent Pythagorean identities:
[tex]\[1 + \tan^2 A = \sec^2 A\][/tex]
[tex]\[1 + \cot^2 A = \csc^2 A\][/tex]
So, the expression now becomes:
[tex]\[\frac{\sec^2 A}{\csc^2 A}\][/tex]
### Step 3: Express secant and cosecant in terms of sine and cosine
Recall the definitions of secant and cosecant:
- [tex]\(\sec A = \frac{1}{\cos A}\)[/tex]
- [tex]\(\csc A = \frac{1}{\sin A}\)[/tex]
Therefore:
[tex]\[\sec^2 A = \left(\frac{1}{\cos A}\right)^2 = \frac{1}{\cos^2 A}\][/tex]
[tex]\[\csc^2 A = \left(\frac{1}{\sin A}\right)^2 = \frac{1}{\sin^2 A}\][/tex]
### Step 4: Substitute these into the expression
Now substituting [tex]\(\sec^2 A\)[/tex] and [tex]\(\csc^2 A\)[/tex] into the expression, we get:
[tex]\[ \frac{\frac{1}{\cos^2 A}}{\frac{1}{\sin^2 A}} = \frac{1 / \cos^2 A}{1 / \sin^2 A} \][/tex]
### Step 5: Simplify the expression
Dividing by a fraction is the same as multiplying by its reciprocal:
[tex]\[ \frac{1 / \cos^2 A}{1 / \sin^2 A} = \left(\frac{1}{\cos^2 A}\right) \times \left(\frac{\sin^2 A}{1}\right) = \frac{\sin^2 A}{\cos^2 A} \][/tex]
### Step 6: Recognize the result
The quotient of [tex]\(\frac{\sin^2 A}{\cos^2 A}\)[/tex] is:
[tex]\[ \frac{\sin^2 A}{\cos^2 A} = \left(\frac{\sin A}{\cos A}\right)^2 = \tan^2 A \][/tex]
### Final Result:
Thus, the given expression simplifies to:
[tex]\[ \frac{1 + \tan^2 A}{1 + \cot^2 A} = \tan^2 A \][/tex]
Hence, the simplified form is:
[tex]\[ \boxed{\tan^2 A} \][/tex]
This is a detailed, step-by-step solution to the problem.
### Step 1: Understand the trigonometric identities involved
1. Tangent and Cotangent:
- [tex]\(\tan A = \frac{\sin A}{\cos A}\)[/tex]
- [tex]\(\cot A = \frac{\cos A}{\sin A}\)[/tex]
2. Pythagorean Identity for Tangent:
- [tex]\(1 + \tan^2 A = \sec^2 A\)[/tex]
3. Pythagorean Identity for Cotangent:
- [tex]\(1 + \cot^2 A = \csc^2 A\)[/tex]
### Step 2: Substitute the identities
Replace [tex]\(1 + \tan^2 A\)[/tex] and [tex]\(1 + \cot^2 A\)[/tex] with their equivalent Pythagorean identities:
[tex]\[1 + \tan^2 A = \sec^2 A\][/tex]
[tex]\[1 + \cot^2 A = \csc^2 A\][/tex]
So, the expression now becomes:
[tex]\[\frac{\sec^2 A}{\csc^2 A}\][/tex]
### Step 3: Express secant and cosecant in terms of sine and cosine
Recall the definitions of secant and cosecant:
- [tex]\(\sec A = \frac{1}{\cos A}\)[/tex]
- [tex]\(\csc A = \frac{1}{\sin A}\)[/tex]
Therefore:
[tex]\[\sec^2 A = \left(\frac{1}{\cos A}\right)^2 = \frac{1}{\cos^2 A}\][/tex]
[tex]\[\csc^2 A = \left(\frac{1}{\sin A}\right)^2 = \frac{1}{\sin^2 A}\][/tex]
### Step 4: Substitute these into the expression
Now substituting [tex]\(\sec^2 A\)[/tex] and [tex]\(\csc^2 A\)[/tex] into the expression, we get:
[tex]\[ \frac{\frac{1}{\cos^2 A}}{\frac{1}{\sin^2 A}} = \frac{1 / \cos^2 A}{1 / \sin^2 A} \][/tex]
### Step 5: Simplify the expression
Dividing by a fraction is the same as multiplying by its reciprocal:
[tex]\[ \frac{1 / \cos^2 A}{1 / \sin^2 A} = \left(\frac{1}{\cos^2 A}\right) \times \left(\frac{\sin^2 A}{1}\right) = \frac{\sin^2 A}{\cos^2 A} \][/tex]
### Step 6: Recognize the result
The quotient of [tex]\(\frac{\sin^2 A}{\cos^2 A}\)[/tex] is:
[tex]\[ \frac{\sin^2 A}{\cos^2 A} = \left(\frac{\sin A}{\cos A}\right)^2 = \tan^2 A \][/tex]
### Final Result:
Thus, the given expression simplifies to:
[tex]\[ \frac{1 + \tan^2 A}{1 + \cot^2 A} = \tan^2 A \][/tex]
Hence, the simplified form is:
[tex]\[ \boxed{\tan^2 A} \][/tex]
This is a detailed, step-by-step solution to the problem.
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.